Taṭwῑr Mawād Ta’lῑm Mahārah al-Kalām li as-Siyāḥah fῑ ḍau` al-Ma’āyir al-Waṭaniyyah li al-Kafā`ah al-Mihniyyah - Meidias Abror Wicaksono; Ab Halim Ahmad; Wa Muna (LISANIA: Journal of Arabic Education and Literature, 2023)
This study aims to develop Arabic-speaking teaching materials for tourism based on the Indonesian National Competency Standards (SKKNI) at the Department of Arabic Literature, State University of Malang. The ADDIE development model was used in this research and development. Data was collected using the instruments of observation, interview, questionnaire, and test. Meanwhile, data analysis techniques include qualitative descriptive data analysis and statistical descriptive. As a result of this research, Arabic language teaching materials for tourism are created according to the needs of students who focus on speaking skills. This teaching material consists of 8 themes: picking up tourists at the airport, hotel check-in, zoo tours, marine tourism, mountain tours, culinary tours, and shopping tours. According to expert opinion, this material is excellent regarding the language used and the content of the teaching materials. Based on the examination of test data using Wilcoxon, it is regarded as effective. In addition, this study recommends further research in Arabic for Tourism with other language skills.